RARE MANIFESTATION OF ANTI-NMDAR ENCEPHALITIS - Ali, Farhan; Waseem, Asra; Sadiq, Hina; Rehman, Areeba (Journal of Ayub Medical College Abbottabad, 2022)
N-methyl-d-aspartate receptor (NMDAR) antibody encephalitis is an autoimmune syndrome with the development of antibody production against the NMDAR, affecting synaptic plasticity and cognition. It has a common association with ovarian teratomas with women being affected disproportionately. We present a case of an eight-year-old female child presented with complaints of fever, altered level of consciousness and choreiform movements. Owing to its common occurrence in the developing world, initially, rheumatic fever was kept in the differential diagnosis and was treated accordingly, but through a series of investigations, was diagnosed as a case of N-methyl-d-aspartate receptor (NMDAR) antibody encephalitis. This case report urges the healthcare providers to keep Anti NMDAR encephalitis as a differential in their minds, while dealing with patients, having chorea as their main clinical manifestation. Owing to its rarity, we have primarily reported it here.